Influence of Culture Conditions on Laccase Production, Growth, and Isoenzymes Patterns in Native White Rot Fungi from the Misiones Rainforest (Argentina) - Fonseca, Maria Isabel; Fariña, Julia Inés; Sanabria, Irma Lorena; Villalba, Laura; Zapata, Pedro Dario
Many biotechnological processes pursuing sustainability search effective, inexpensive and environmentally friendly alternatives to replace conventional practices. Lignocellulolytic white rot fungi can serve for this task through their enzymatic system including laccase (Lac). One of purposes of biotechnological enzymes production processes is usually to find the best growing and secretion conditions for a particularly selected fungus. In this work, different fungi isolated from the Misiones rainforest (Coriolus versicolor f. antarcticus BAFC-266, Ganoderma applanatum strain F, Phlebia brevispora BAFC-633 and Pycnoporus sanguineus BAFC-2126) were incubated at different temperatures (25, 29, 33°C) and pHs (3.5, 4.5, 5.5) under static conditions for 7, 10 and 14 days to evaluate their growing ability and Lac production. Results revealed specific favorable conditions for growth and protein secretion depending on the fungus under consideration, making necessary to adjust these parameters for each particular case. The combined effect of these cultivation parameters showed a marked influence on the secreted Lac activity by P. brevispora BAFC 633, with the highest activity (~ 240 U/l) at 29ºC and pH 4.5 at the 10th day of cultivation. The presence of Lac isoenzymes also depended on the pH, temperature and time of cultivation for the different tested fungi. Fil: Fonseca, Maria Isabel. Universidad Nacional de Misiones. Facultad de Ciencias Exactas Químicas y Naturales. Departamento de Bioquímica Clínica. Laboratorio de Biotecnología Molecular; Argentina; Fil: Fariña, Julia Inés. Universidad Nacional de Misiones. Facultad de Ciencias Exactas Químicas y Naturales. Departamento de Bioquímica Clínica. Laboratorio de Biotecnología Molecular; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico - CONICET - Tucumán. Planta Piloto de Procesos Industriales Microbiológicos (i); Argentina; Fil: Sanabria, Irma Lorena. Universidad Nacional de Misiones. Facultad de Ciencias Exactas ...